Investigation and Case Study for Repairs and Remedial Measures in Internal and External Plastering - Manikandan Srinivasan (International Journal of Scientific Research in Civil Engineering, 2023)
A variety of external plastering types exist in construction industries, where premix cement plaster is adopted in most of the buildings. External plaster is mainly used to cover uneven block surfaces, increase durability, and get a smooth and aesthetic external surface. It is obvious, this is a highly challenging activity in UAE due to high atmosphere temperature and Humidity. Activity needs to be performed with utmost care to avoid defects, if any failure to abide correct procedure may affect the external surfaces and increase the extra cost / time for repair and rectification works. In some cases, it may lead to the project delay and completion. Hence, in this article, we explore the case study of external plastering defects, corrective and preventive measures learned in one of the projects.
Keywords: Technical Writing; Civil Engineering; Construction Industries